Changes in Left Ventricular Wall Movement after Acute Myocardial Infarction Measured by Reflected Ultrasound. Issue 5779 (9th October 1971) - Wharton, Christopher F. P.; Smithen, Charles S.; Sowton, Edgar
Abstract : Serial measurements of left ventricular posterior wall movement were made in eight patients with acute myocardial infarction by an ultrasound technique. Maximum posterior wall velocity and excursion were decreased during the first 36-hour period after infarction. In two patients a reduction in posterior wall velocity was associated with an increased pulmonary artery pressure and as the pressure returned towards normal the posterior wall motion also improved. It is suggested that this method provides a convenient, non-invasive bedside assessment of left ventricular function after acute myocardial infarction.